2022
DOI: 10.3389/fmicb.2021.737197
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Psychiatric Disorders: A Two-Sample Mendelian Randomization Study

Abstract: Evidence supports the observational associations of gut microbiota with a variety of psychiatric disorders, but the causal nature of such associations remains obscure. Aiming to comprehensively investigate their causal relationship and to identify specific causal microbe taxa for psychiatric diseases, we conducted a two-sample Mendelian randomization (MR) analysis of gut microbiome with 15 psychiatric diseases. Specifically, the microbiome genome-wide association study (GWAS) in 18,473 individuals from the MiB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 69 publications
0
88
1
Order By: Relevance
“…In the current study, the difference of taxa was significant between SMPS and VPA groups, especially in Prevotellaceae and Lachnospiraceae_NK4A136_group. One study has reported that Prevotellaceae was the specific causal microbe taxa for autism spectrum disorder (Ni et al, 2021). In comparative studies between ASD and normal children, the relative abundance of Prevotellaceae in the ASD children was significantly lower than that of control children, whereas our study indicated that SMPS intervention was able to increase the abundance of Prevotellaceae (Pulikkan et al, 2018;Qiao et al, 2018;Sun et al, 2019).…”
Section: Discussioncontrasting
confidence: 50%
“…In the current study, the difference of taxa was significant between SMPS and VPA groups, especially in Prevotellaceae and Lachnospiraceae_NK4A136_group. One study has reported that Prevotellaceae was the specific causal microbe taxa for autism spectrum disorder (Ni et al, 2021). In comparative studies between ASD and normal children, the relative abundance of Prevotellaceae in the ASD children was significantly lower than that of control children, whereas our study indicated that SMPS intervention was able to increase the abundance of Prevotellaceae (Pulikkan et al, 2018;Qiao et al, 2018;Sun et al, 2019).…”
Section: Discussioncontrasting
confidence: 50%
“…These include, for example, the statistical problems derived from the fact that, in MR, the randomization process is confided to the natural distribution in the population of genetic variants, which may sometimes be, in fact, nonrandom (e.g. due to linkage disequilibrium, or ‘cryptic relatedness’), which have been discussed in detail in the MR literature (Voight and Pritchard, 2005; Nitsch et al , 2006; Boef et al , 2015). Furthermore, the heterogeneity of the populations included in the MR studies may represent a confounder in the analyses performed by the papers that we reviewed.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Nevertheless, this study has some limitations. First, as SNPs in the MiBioGen study less than 5 × 10 –8 are not sufficient for MR analysis, the significance level of gut microbiota IV selection is set at 1 × 10 –5 instead of 5 × 10 –8 , which is the same as that in a previous publication ( Ni et al, 2021 ). However, the F-statistics are guaranteed to be > 10 to exclude potential weak instrument bias and make the statistical results more robust ( Burgess and Thompson, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial taxa were classified and analyzed at six levels (phylum, class, order, family, genus, and species) based on SNPs available in the gut microbiome GWAS summary data. Candidate IVs were identified at a significance level of P < 1.0 × 10 –5 according to the previously published studies ( Sanna et al, 2019 ; Ni et al, 2021 ). The parameters of the clump function in the R package were set at r 2 < 0.1 and kb = 500 kb, guaranteeing the independence of each IV, which was the same as in a previous publication, to minimize the impact of linkage disequilibrium violating the randomized allele allocation ( Ni et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation